Acute obturator internus muscle strain in a rugby player: a case report - Velleman, M. D.; Jansen Van Rensburg, A.; Janse Van Rensburg, D. C.; Strauss, O. (The Journal of Sports Medicine and Physical Fitness, 2015)
A 28-year-old male rugby player presented with severe onset of right hip pain when he fell awkward after a ruck during an international match. A rare case of an acute strain of the obturator internus muscle, a deep muscle of the hip joint, is reported, which resolved completely after a period of rest and intense active physical therapy.